2007
DOI: 10.1093/carcin/bgm194
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide detection of testis- and testicular cancer-specific alternative splicing

Abstract: Alternative pre-messenger RNA (mRNA) splicing is a key molecular event that allows for protein diversity and plays important roles in development and disease. Alternative pre-mRNA splicing regulations during spermatogenesis and alternative pre-mRNA splicing etiology in testicular tumorigenesis are yet to be characterized. By genome-wide analysis, here we describe alternative splicing features that distinguish distinctive patterns of alternative pre-mRNA splicing among human testis, testicular cancer and mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Evidence for wide changes in alternative splicing in cancer is present in EST databases, where a large fraction of variants are actually tumor specific. [50][51][52][53] Interestingly, Ritchie and collaborators recently found that the number of different splicing variants produced from a single gene was higher in a cancer tumor than in its normal counterpart tissue. 52 In contrast, an EST-based study by Kim and collaborators indicated that, in general, alternative splicing was less prevalent in cancerous than normal tissues.…”
Section: Widespread Alteration Of Splicing In Cancermentioning
confidence: 99%
“…Evidence for wide changes in alternative splicing in cancer is present in EST databases, where a large fraction of variants are actually tumor specific. [50][51][52][53] Interestingly, Ritchie and collaborators recently found that the number of different splicing variants produced from a single gene was higher in a cancer tumor than in its normal counterpart tissue. 52 In contrast, an EST-based study by Kim and collaborators indicated that, in general, alternative splicing was less prevalent in cancerous than normal tissues.…”
Section: Widespread Alteration Of Splicing In Cancermentioning
confidence: 99%
“…AS is a common phenomenon and more than 90% human genes are alternatively spliced (Pan et al, 2008;Wang et al, 2008). It is known that AS is involved in numerous human diseases (Kim et al, 2007), thus accumulating evidence revealed that aberrant splicing contributes to human neoplasms (Miura et al, 2011;Xing, 2007;Kim et al, 2007;Venables, 2006;He et al, 2007;Srebrow & Kornblihtt, 2006). However, in only few cases it has been proved, e.g.…”
Section: Alternative Splicing Of Dcs and Tumorigenesis In Bccmentioning
confidence: 99%
“…In light of this, oligonucleotide microarrays containing exon junction probes may be a powerful tool to investigate tissue-specific regulation of AS taking place in BCC (Nagao et al, 2005). Literature data may suggest that AS should be regarded as a potential source for new clinical diagnostic, prognostic and therapeutic strategies in cancer (He et al, 2007).…”
Section: Alternative Splicing Of Dcs and Tumorigenesis In Bccmentioning
confidence: 99%
“…3 Particularly, the splice variants differ between cancer and normal corresponding tissues. 4,5 Cancerspecific splice variants are thus of significant interest as they may be involved in pathogenesis and may further potentially be used as biomarkers and generate novel targets for therapy. Because immune recognition of antigenic epitopes is highly specific, alternative exon splicing could provide the structural basis for expression of novel amino-acid sequences not subject to self repertoire tolerance.…”
mentioning
confidence: 99%